IgG myeloma presenting as ulcerative colitis. Issue 9 (September 1977) - Haeney, M R; Ross, I N; Thompson, R A; Asquith, P
Abstract : Two patients who presented with ulcerative colitis are described. Both were found to have evidence of IgG monoclonal gammopathy and Bence-Jones proteinuria. This association has been reported previously only in the presence of myelomatous infiltration of the gastrointestinal tract or in amyloidosis, and hence the cases reported appear to be unique.